Survey of glyphosate-, atrazine- and lactofen-resistance mechanisms in Ohio waterhemp (Amaranthus tuberculatus) populations. Issue 3 (14th March 2019) - Murphy, Brent P.; Larran, Alvaro S.; Ackley, Bruce; Loux, Mark M.; Tranel, Patrick J.
Abstract: Herbicide resistance within key driver weeds, such as common waterhemp [ Amaranthus tuberculatus (Moq.) Sauer var. rudis (Sauer) Costea and Tardif ], constrains available management options for crop production. Routine surveillance for herbicide resistance provides a mechanism to monitor the development and spread of resistant populations over time. Furthermore, the identification and quantification of resistance mechanisms at the population level can provide information that helps growers develop effective management plans. Populations of Amaranthus spp., including A. tuberculatus, redroot pigweed ( Amaranthus retroflexus L.), and Palmer amaranth ( Amaranthus palmeri S. Watson), were collected from 51 fields in Ohio during the 2016 growing season. Twenty-four A. tuberculatus populations were screened for resistance to the herbicides lactofen, atrazine, and glyphosate. Phenotypically resistant plants were further investigated to determine the frequency of known resistance mechanisms. Resistance to lactofen was infrequently observed throughout the populations, with 8 of 22 populations exhibiting resistant plants. Within those eight resistant populations, the ΔG210 resistance mechanism was observed in 17 of 30 phenotypically resistant plants, and the remainder lacked all known resistance mechanisms. Resistance to atrazine was observed in 12 of 15 populations; however, a target-site resistance mechanism was not observed in these populations. Resistance to glyphosate was observed in all populations. Gene amplification was the predominant glyphosate-resistance mechanism (147 of 322 plants) in the evaluated populations. The Pro-106-Ser mutation was identified in 24 plants, half of which also possessed gene amplification. In this study, molecular screening generally underestimated the phenotypically observed resistance. Continued mechanism discovery and marker development is required for improved detection of herbicide resistance through molecular assays.